ANALISIS MINAT BELAJAR SISWA SMA PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Devia Haedi Pyarsha; Dadang Rahman Munandar (SIGMA, 2021)
This study aims to analyze students interest in learning mathematics, especially in the material of three variable linear equation systems. The subjects of this study were X class high school students in one of the public high schools in Karawang. The research instrument used was students interest with 18 item statements containing positive statements and negative statements and containing 4 (four) indicators of interest in learning, including : 1) Feelings of pleasure/like, 2) Attention, 3) Interest, and 4) Student involvement as well as the results of observations during the mathematics learning process, especially in the SPLTV material. The results obtained in this study indicate that each indicator of students interest in learning falls into the sufficient category with a proportion of more than 50%.